The Implementation of Task-Based Language Teaching (TBLT) in Arabic Language Instruction at Madrasah Aliyah: a Qualitative Analysis of Processes and Challenges - Ela Saela; Muhamad Maulana Yusup; Zakia Jauharotul Munfarida (UIN Sunan Gunung Djati Bandung, 2026)
This study aims to explain the planning and implementation processes of the Task-Based Language Teaching (TBLT) approach in Arabic language instruction at Madrasah Aliyah (MA), as well as to identify the challenges that arise from the perspectives of teachers, students, and the learning environment. The research focuses on analyzing the three main stages of TBLT: the Pre-Task phase, the Task Cycle, and the Language Focus. A descriptive qualitative method was employed, utilizing observation, in-depth interviews, and documentation as data collection techniques. The data were analyzed using the Miles and Huberman model, involving data reduction, data display, and conclusion drawing, and were validated through source and technique triangulation. The findings indicate that TBLT is effective in improving students’ speaking skills, language fluency, motivation, and engagement when tasks are designed to be authentic and relevant to students’ lives. Teachers are able to facilitate communicative interaction through group work, negotiation of meaning, and scaffolding. However, the implementation still faces several obstacles, including teachers’ limited understanding of TBLT, difficulties in designing authentic tasks, students’ limited vocabulary, and insufficient learning facilities. The effectiveness of TBLT greatly depends on teacher readiness, institutional support, and the quality of task design; therefore, training and the provision of contextual learning resources are necessary.